The Faktor-faktor yang berhubungan dengan kepatuhan perawat dalam kelengkapan dokumentasi surgical patient safety fase sign out di instalasi bedah sentral - Priyantoro, Berta; Melati, Nimsi (Jurnal Kesehatan, 2024)
Patient safety has becomes a global issue including in hospitals, so this issue brings a new paradigm of service quality. Especially in the operating room. One of the tools to assess the implementation of services in the operating room, namely surgical patient safety checklist. In surgical patient safety checklist there are 3 phases, the sign out phase is not documented completely. To know the factors related to nurses compliance with documentation of surgical patient safety sign out phase in the Central Surgery Installation. This was a correlational research design with cross sectional approach. Respondents as many as 40 people with total population sampling. The method used was observation of respondents with 5 statement in that instrument. Analysis test with age and education level using the Kolmogorov smirnov test, gender using chi square test, and the years of service using fisher exact test. The test results of P for each variable, namely age (p=0,916), gender (p=0.822), education level (p=0.997) and years of service (p=1,000). Based on the results, the p-values>α (0.05). There is no correlation of age, gender, education level and years of service on compliance with the completeness of the sign out phase of surgical patient safety documentation in the Central Surgery Installation. Hospitals are advised to hold training, monitoring and evaluating related to Surgical Patient Safety.